PENGARUH PROMOSI KESEHATAN DENGAN MEDIA VIDEO TERHADAP TINGKAT PENGETAHUAN KADER DALAM PENCEGAHAN STUNTING - Nuralam, Nuralam; Susilawati, Dewi (Jurnal Ilmiah Kesehatan, 2022)
Background: Stunting is a condition in which toddlers have a length or height that is less than their age. Chronic nutritional problems causing stunting are influenced by various factors, including socio-economic conditions, maternal nutrition during pregnancy, infant feeding practices, and nutritional deficiencies in infants, which may later result in difficulties in achieving optimal physical and cognitive development. Objective: This study aims to determine the effect of health promotion using audiovisual media on the knowledge of Posyandu cadres in preventing stunting. Method: The study used a quantitative research design with a pre-experimental design using the One Group Pretest-Posttest Only Design. The sample consisted of 15 Posyandu cadres from Susukan sub-district, East Jakarta, and was analyzed using paired t-tests. Data collection was conducted through video media. The study was conducted in June 2022. Results: The average knowledge of stunting prevention among Posyandu cadres before health promotion using audiovisual media was 5.30, and after health promotion, it remained at 5.30. Conclusion and Recommendation: Health promotion using video media has no significant effect on the level of knowledge among cadres in preventing stunting. Therefore, it is recommended to enhance high-quality health promotion related to cadres' knowledge in preventing stunting and to encourage active community participation in integrated services for Posyandu cadres. Keywords: Promotion, Audiovisual, Stunting, Posyandu Cadres